2023
DOI: 10.14218/jcth.2022.00006s
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Value of Protein Post-Translational Modifications in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a common malignant tumor with high incidence and cancer mortality worldwide. Post-translational modifications (PTMs) of proteins have a great impact on protein function. Almost all proteins can undergo PTMs, including phosphorylation, acetylation, methylation, glycosylation, ubiquitination, and so on. Many studies have shown that PTMs are related to the occurrence and development of cancers. The findings provide novel therapeutic targets for cancers, such as glypican-3 and muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…For HCC, the discovery of GPC3 as a promising tumor-associated antigen because GPC3 is over-expressed in cancerous tissues and is significantly associated with poor prognostic disease-free survival and overall survival[ 67 , 68 ]. Indeed, clinical and basic studies have demonstrated that GPC3 is a carcino- embryonic proteoglycan anchored to the membrane of HCC cells and is involved in promoting HCC growth and invasion through a variety of signaling cascades; including the Wnt pathway, which plays a well-known role in embryogenesis[ 69 , 70 ]. It was found that the up-regulated expression of GPC3mRNA, gene or protein in the tissues or serum of patients with liver cancer could not only specifically diagnose liver cancer, but also had a bad prognosis with the patients with liver cancer[ 71 ].…”
Section: Hepatic Gpc3 Signallingmentioning
confidence: 99%
“…For HCC, the discovery of GPC3 as a promising tumor-associated antigen because GPC3 is over-expressed in cancerous tissues and is significantly associated with poor prognostic disease-free survival and overall survival[ 67 , 68 ]. Indeed, clinical and basic studies have demonstrated that GPC3 is a carcino- embryonic proteoglycan anchored to the membrane of HCC cells and is involved in promoting HCC growth and invasion through a variety of signaling cascades; including the Wnt pathway, which plays a well-known role in embryogenesis[ 69 , 70 ]. It was found that the up-regulated expression of GPC3mRNA, gene or protein in the tissues or serum of patients with liver cancer could not only specifically diagnose liver cancer, but also had a bad prognosis with the patients with liver cancer[ 71 ].…”
Section: Hepatic Gpc3 Signallingmentioning
confidence: 99%
“… 4 Post-translational modifications (PTMs), such as phosphorylation, acetylation, methylation, glycosylation, and ubiquitination have a major impact on protein function and have been shown to be associated with the development of various diseases including tumors, neurological diseases, and metabolic diseases. 5 …”
Section: Introductionmentioning
confidence: 99%
“…4 Post-translational modifications (PTMs), such as phosphorylation, acetylation, methylation, glycosylation, and ubiquitination have a major impact on protein function and have been shown to be associated with the development of various diseases including tumors, neurological diseases, and metabolic diseases. 5 Journal of Hepatocellular Carcinoma 2024:11 [15][16][17][18][19][20][21][22][23][24][25][26][27] Protein methylation is a common PTM that has a pivotal role in regulation of cellular functions. 6,7 In particular, accumulating evidence indicates that protein arginine methylation is an indispensable model of methylation related-PTM, which is regulated by a family of enzymes, named protein arginine methyltransferases 1-9 (PRMT1-9).…”
Section: Introductionmentioning
confidence: 99%